Coulomb blockade phenomena observed in supported metallic nanoislands - Schneider, Wolf-Dieter (Frontiers in Physics, 2013)
The electron transport properties of single crystalline metallic nanostructures in the Coulomb blockade (CB) regime have been investigated by low-temperature scanning tunneling spectroscopy. To this end, nanoscale flat-top Pb islands with well-defined geometries are grown on NaCl-covered Ag(111) substrates. The tunneling spectra acquired at 4.6 K on the Pb nanoislands reflect the presence of single electron tunneling processes across the double-barrier tunnel junction (DBTJ). By a controlled change of the tip-island tunnel distance, the spectra display the characteristic evolution from CB to Coulomb staircase (CS) regime. Simulations within the semi-classical orthodox theory allow us to extract quantitatively the parameters characterizing the DBTJ, i.e., the resistances, capacitances, and the residual charge Q0. Manipulation of Q0 is achieved by controlled application of voltage pulses on the Pb islands. Moreover, under specific tunneling conditions, the influence of the tip-island junction on Q0 is revealed in topographic images of the Pb islands.